Project-Based Blended Learning to Improve Reading Interest and Writing Skills Research Proposal - Ari Sutisyana; Yahya Eko Nopiyanto; Arwin arwin; Yarmani yarmani (UNIB Press, 2022)
The purpose of this research was to increase reading interest and research proposal writing skills. The type of research used is classroom action with two cycles. The participants in this study were all seventh-semester physical education students who attended the proposal seminar lecture, totaling 80 students. Data collection techniques used observation guides, questionnaires, and product assessments in the form of research proposals. Data analysis techniques using categories and percentages. Based on the results of data analysis, it was known that in cycle 1 students' interest in reading was in the medium category, and cycle 2 is in the high category. Meanwhile, students' research proposal writing skills in cycle 1 was in the medium category, and in cycle 2 was in the high category. Classical completeness in cycle 1 was 18.75% for reading interest, and 17.5% for research proposal writing skills. Meanwhile, classical completeness in cycle 2 in this study was 81.25% for reading interest, and 82.5% for research proposal writing skills. So it can be concluded that the application of project-based blended learning increased reading interest and research proposal writing skills.